Penerapan Ergonomi pada Penjual Jamu Gendong dengan Metode RULA dan REBA di Kaliawi Persada - Fauzan, Haroni; Sundari, Susanti; Hafizulghani, Muhammad; Farizi, Al; Buari, Jevri; Nashiruddin, Muhammad (Fakultas Teknik Universitas Tulang Bawang, 2026)
A risk of musculoskeletal disorders (MSDs) due to non-ergonomic work postures was found in herbal medicine sellers. This study aims to analyze the posture and ergonomic risk levels using RULA, REBA, and Nordic Body Map (NBM) through observation and interviews with three respondents (aged 21, 33, and 63 years) who work an average of 2–3 hours per day with a load of 7 kg. The results of the study using Rula and Reba showed that the work posture was not fully ergonomic, with Rula values ​​of 4 and Reba values of 9. RULA and REBA values ​​indicate a moderate to high risk level, especially in elderly respondents. Although there have been no significant musculoskeletal complaints, the potential for musculoskeletal disorders can increase if work habits are not immediately corrected. It is necessary to apply ergonomic principles such as using a more ergonomic carrier (wide and soft straps), adjusting the load balance, taking active breaks and stretching, using alternative pushing aids (trolleys) on flat areas. Overall, the workload is still considered safe according to metabolic energy, but body efficiency decreases with age. Keywords: Ergonomics, Herbal Drink Seller, NBM, RULA, REBA